(x-6)(x-3)=-2

Simple and best practice solution for (x-6)(x-3)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-6)(x-3)=-2 equation:


Simplifying
(x + -6)(x + -3) = -2

Reorder the terms:
(-6 + x)(x + -3) = -2

Reorder the terms:
(-6 + x)(-3 + x) = -2

Multiply (-6 + x) * (-3 + x)
(-6(-3 + x) + x(-3 + x)) = -2
((-3 * -6 + x * -6) + x(-3 + x)) = -2
((18 + -6x) + x(-3 + x)) = -2
(18 + -6x + (-3 * x + x * x)) = -2
(18 + -6x + (-3x + x2)) = -2

Combine like terms: -6x + -3x = -9x
(18 + -9x + x2) = -2

Solving
18 + -9x + x2 = -2

Solving for variable 'x'.

Reorder the terms:
18 + 2 + -9x + x2 = -2 + 2

Combine like terms: 18 + 2 = 20
20 + -9x + x2 = -2 + 2

Combine like terms: -2 + 2 = 0
20 + -9x + x2 = 0

Factor a trinomial.
(4 + -1x)(5 + -1x) = 0

Subproblem 1

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Subproblem 2

Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5

Solution

x = {4, 5}

See similar equations:

| a^2-8a=-16 | | 2(3x+6x)=25 | | 102/4 | | 105=-5(4b+7) | | (X+30)+(180-3x)+(1X)=180 | | 5v=11+3u | | 3-(-6x)=4x+9 | | 2cosx-4=0 | | f(a)=2a^2-16a+32 | | 2x(y-4)=2 | | 1/4(8x-20)=7 | | 2Z^2+4z-70=0 | | 16z+42=80 | | 2y+2x-3=0 | | X=-30+3x | | (2-y/5)=1 | | -24=-4x+2(x+5) | | 15m+21=96 | | 15m+12=96 | | 8x-11=3x-6 | | -4d+2(d+3)=-14 | | 1-5/2x=0 | | (X+30)+(180-3x)=180 | | 8k-12=60 | | cx+fy=mforx | | http://www.geteasysolution.com/6x^3-4x^2-2x=0 | | 2x+y=103 | | 6x+9x+2x+3=11x+30 | | 15b+12=42 | | -3mx-18+4xm+6-mx=12 | | 100x+20y+z=100 | | x-(x*0.01)-((((x*12)*0.18)-13500)/12)=8791.25 |

Equations solver categories